Preparation method and application of CD-MOFs and AgNPs-coated CD-MOFs, and food preservative film

Non-toxic nanoscale CD-MOFs were prepared by controlling the concentration and ethanol addition rate, and reacting with silver nitrate under dark conditions to generate AgNPs@CD-MOFs, which solved the problem of using higher toxic size regulators in the prior art and achieved Highly effective antibacterial and low toxicity effects of food plastic wrap.

CN119306963AActive Publication Date: 2025-01-14NANJING UNIV OF FINANCE & ECONOMICS
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411422241.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-12
Publication Date
2025-01-14
Estimated Expiration
2044-10-12

AI Technical Summary

Technical Problem

The preparation of existing nanoscale CD-MOFs requires the use of highly toxic size regulators, which cannot be directly applied to food preservation.

Method used

By controlling the concentration of cyclodextrin and potassium hydroxide and the ethanol addition rate, heating and stirring in anhydrous ethanol environment, non-toxic nanoscale CD-MOFs were prepared, and reacted with silver nitrate under dark conditions to form silver doping. Nanoscale cyclodextrin metal organic frame (AgNPs@CD-MOFs) is used for the preparation of food plastic wrap.

Benefits of technology

Non-toxic nanoscale CD-MOFs and AgNPs@CD-MOFs were successfully prepared, which improved the antibacterial properties and low toxicity of food plastic wrap and extended the storage quality of fresh fruits and vegetables.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119306963A_ABST
    Figure CN119306963A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of food preservation, in particular to a preparation method and application of CD-MOFs and AgNPs coated CD-MOFs, and a food preservative film. The preparation method provided by the invention comprises the following steps: mixing cyclodextrin, potassium hydroxide and water to obtain a mixed solution; the concentration of cyclodextrin in the mixed solution is 2.5 to 12.5 mmol / L; the concentration of potassium hydroxide in the mixed solution is 20-100 mmol / L; and heating the mixed solution in the environment of first absolute ethyl alcohol, and adding second absolute ethyl alcohol into the mixed solution to obtain the nanoscale cyclodextrin metal organic framework, the second absolute ethyl alcohol is added through a peristaltic pump; the rotating speed of the peristaltic pump is 25 to 100 rpm; the mixed solution is not in direct contact with the first absolute ethyl alcohol. According to the preparation method, the non-toxic nanoscale CD-MOFs can be prepared without adopting a size regulator, and can be directly applied to the field of food preservation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of food preservation, and in particular to a preparation method and application of CD-MOFs and AgNPs@CD-MOFs, and a food preservative film. Background Art

[0002] At present, the synthesis of nano-scale CD-MOFs (cyclodextrin metal organic frameworks) mostly requires the use of size regulators, which can effectively reduce the size of the generated CD-MOFs. Size regulators can affect the attachment of ligands to metal particles by interfering with the deprotonation of organic ligands. At the same time, size regulators can also be used as surface capping agents to prevent further growth of crystals. However, conventional size regulators in the prior art mainly include high molecular weight polyethylene glycol and triethylamine, etc. These size regulators are not suitable for direct application in food preservation because they all have certain toxicity and cannot be completely eliminated during the preparation process. Summary of the invention

[0003] The purpose of the present invention is to provide a preparation method and application of CD-MOFs and AgNPs@CD-MOFs, and a food preservative film. The preparation method can prepare non-toxic nanoscale CD-MOFs without using a size regulator, and can be directly applied to the field of food preservation.

[0004] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0005] The present invention provides a method for preparing nano-scale cyclodextrin metal organic frameworks (CD-MOFs), comprising the following steps:

[0006] Mixing cyclodextrin, potassium hydroxide and water to obtain a mixed solution; the concentration of cyclodextrin in the mixed solution is 2.5 to 12.5 mmol / L; the concentration of potassium hydroxide in the mixed solution is 20 to 100 mmol / L;

[0007] After heating the mixed solution in the environment of the first anhydrous ethanol, adding the second anhydrous ethanol to the mixed solution to obtain the nano-cyclodextrin metal organic framework; the second anhydrous ethanol is added by a peristaltic pump; the rotation speed of the peristaltic pump is 25-100 rpm;

[0008] The mixed liquid is not in direct contact with the first anhydrous ethanol.

[0009] Preferably, the molar ratio of cyclodextrin to potassium hydroxide is 1:8.

[0010] Preferably, the mixing is carried out under stirring;

[0011] The stirring speed is 100-400 rpm, and the time is 30-120 min;

[0012] Preferably, the mixing further comprises filtering;

[0013] The filtration adopts a 0.45 μm organic membrane.

[0014] Preferably, the heating temperature is 50-90° C. and the heating time is 24-72 hours.

[0015] The present invention also provides a method for preparing a silver-doped nanoscale cyclodextrin metal organic framework (AgNPs@CD-MOFs), comprising the following steps:

[0016] After mixing the nano-cyclodextrin metal organic framework dispersion and the silver nitrate solution, the mixture is cultured in the dark to obtain the silver-doped nano-cyclodextrin metal organic framework;

[0017] The nano-cyclodextrin metal-organic framework in the nano-cyclodextrin metal-organic framework dispersion is a nano-cyclodextrin metal-organic framework dispersion prepared by the preparation method described in the above technical solution.

[0018] Preferably, the mass ratio of the nano-cyclodextrin metal-organic framework in the nano-cyclodextrin metal-organic framework dispersion to the silver nitrate in the silver nitrate solution is (10-50):1.

[0019] Preferably, the culture is carried out under shaking conditions, the shaking frequency is 50 to 200 rpm, and the time is 12 to 72 hours.

[0020] The present invention also provides the use of the silver-doped nano-cyclodextrin metal organic framework prepared by the preparation method described in the above technical solution in food preservative film.

[0021] The present invention also provides a food preservative film, the preparation raw materials of which include silver-doped nano-cyclodextrin metal organic framework, polylactic acid and polyethylene glycol;

[0022] The mass ratio of the silver-doped nano-cyclodextrin metal organic framework, polylactic acid and polyethylene glycol is (0.2-1.6):8:0.8.

[0023] The present invention provides a method for preparing a nano-scale cyclodextrin metal organic framework, comprising the following steps: mixing cyclodextrin, potassium hydroxide and water to obtain a mixed solution; the concentration of cyclodextrin in the mixed solution is 2.5-12.5 mmol / L; the concentration of potassium hydroxide in the mixed solution is 20-100 mmol / L; after heating the mixed solution in an environment of a first anhydrous ethanol, a second anhydrous ethanol is added to the mixed solution to obtain the nano-scale cyclodextrin metal organic framework; the second anhydrous ethanol is added via a peristaltic pump; the rotation speed of the peristaltic pump is 25-100 rpm; the mixed solution and the first anhydrous ethanol are not in direct contact. The present invention successfully prepares nano-scale CD-MOFs by controlling the concentrations of CD and KOH and the rate of ethanol addition. The formation of crystals is directly related to the critical supersaturation concentration of the solution. First, control the concentrations of CD and KOH and the speed of ethanol addition. + The initial concentration of can directly affect the rate of nucleation and crystal growth. The appropriate concentration of CD and K + It is conducive to the formation of nano-scale CD-MOF. + Increased nucleation rate, but shortened K + The diffusion path length is shortened, resulting in faster crystal growth rate. In addition, low concentrations of CD and K + Leading to reduced crystal nucleation, CD and K + Aggregation around a few nuclei leads to an increase in crystal size. Both high and low concentrations are not conducive to the production of nanosized CD-MOFs. Secondly, the speed of ethanol addition may affect the initial crystallization and recrystallization processes. Specifically, a faster addition rate (100 rpm) may lead to secondary nucleation and the formation of immature crystals, while a slower addition rate may slow down the precipitation of crystals, both of which are not conducive to the generation of CD-MOFs of uniform size.

[0024] The present invention also provides a method for preparing a silver-doped nano-cyclodextrin metal-organic framework, comprising the following steps: mixing a nano-cyclodextrin metal-organic framework dispersion and a silver nitrate solution, and culturing under dark conditions to obtain the silver-doped nano-cyclodextrin metal-organic framework; the nano-cyclodextrin metal-organic framework in the nano-cyclodextrin metal-organic framework dispersion is a nano-cyclodextrin metal-organic framework dispersion prepared by the preparation method described in the above technical scheme. Due to the framework limitation and good dispersibility of nano-sized CD-MOFs, the size of nano-silver particles is reduced (can reach 1 to 2 nm), which in turn leads to an improvement in the antibacterial ability of nano-silver. In addition, nano-silver is confined in the framework, thereby hindering contact with cells. Therefore, the silver-doped nano-cyclodextrin metal-organic framework prepared by the preparation method has good antibacterial and low toxicity properties.

[0025] The present invention also provides a food preservative film, the preparation raw materials include silver-doped nano-cyclodextrin metal organic framework, polylactic acid and polyethylene glycol; the mass ratio of the silver-doped nano-cyclodextrin metal organic framework, polylactic acid and polyethylene glycol is (0.2-1.6):8:0.8. Compared with PE, the food preservative film of the present invention can improve the storage quality of fresh fruit and vegetable food (Agaricus bisporus). BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 The scanning electron microscope (SEM) images, transmission electron microscope (TEM) images and energy dispersive X-ray spectroscopy (EDS) images of the γ-CD-MOFs described in Examples 1 to 11 are shown;

[0027] Figure 2 TEM image of γ-CD-MOFs described in Example 5 and particle size distribution diagram of γ-CD-MOFs described in Example 5;

[0028] Figure 3 The SEM image (a), TEM image (b), EDS image of a single AgNPs@γ-CD-MOFs (c), EDS point scan image of a single AgNPs@γ-CD-MOFs (d), EDS surface scan image of a single AgNPs@γ-CD-MOFs - C element distribution map (e), O element distribution map (f), K element distribution map (g) and Ag element distribution map (h) of the AgNPs@γ-CD-MOFs described in Example 16;

[0029] Figure 4 N2 adsorption-desorption curves (a) and pore size distribution curves (b) of the γ-CD-MOFs described in Example 1 and the AgNPs@γ-CD-MOFs described in Example 16;

[0030] Figure 5 The antibacterial activity (a) and cell viability (b) of AgNPs@γ-CD-MOFs described in Example 16;

[0031] Figure 6 Visible light and ultraviolet transmittance (a), water vapor transmittance (b) and oxygen transmittance (c) of the food preservative films of Examples 23 to 26 and Comparative Example 1;

[0032] Figure 7 It is a bar graph showing the antibacterial rate of the food preservative film described in Example 25 and Comparative Example 1 against different types of bacteria;

[0033] Figure 8 Save the effect picture of Agaricus bisporus. DETAILED DESCRIPTION

[0034] The present invention provides a method for preparing nano-scale cyclodextrin metal organic frameworks (CD-MOFs), comprising the following steps:

[0035] Mixing cyclodextrin, potassium hydroxide and water to obtain a mixed solution; the concentration of cyclodextrin in the mixed solution is 2.5 to 12.5 mmol / L; the concentration of potassium hydroxide in the mixed solution is 20 to 100 mmol / L;

[0036] After heating the mixed solution in the environment of the first anhydrous ethanol, adding the second anhydrous ethanol to the mixed solution to obtain the nano-cyclodextrin metal organic framework; the second anhydrous ethanol is added by a peristaltic pump; the rotation speed of the peristaltic pump is 25-100 rpm;

[0037] The mixed liquid is not in direct contact with the first anhydrous ethanol.

[0038] In the present invention, unless otherwise specified, all preparation raw materials are commercially available products well known to those skilled in the art.

[0039] The invention mixes cyclodextrin, potassium hydroxide and water to obtain a mixed solution; the concentration of cyclodextrin in the mixed solution is 2.5-12.5 mmol / L; the concentration of potassium hydroxide in the mixed solution is 20-100 mmol / L.

[0040] In the present invention, the cyclodextrin is preferably γ-cyclodextrin (γ-CD). In an embodiment of the present invention, the γ-CD is purchased from Shanghai Yuanye Biotechnology Co., Ltd. (Shanghai, China). In an embodiment of the present invention, the purity of the potassium hydroxide is 99.99%. In the present invention, the water is preferably ultrapure water.

[0041] In the present invention, the mixing is preferably carried out under stirring, and the stirring speed is preferably 100 to 400 rpm, more preferably 300 rpm; the stirring time is preferably 30 to 120 min, more preferably 1 h. The present invention does not have any special restrictions on the stirring method, and it can be carried out in a manner familiar to those skilled in the art. In an embodiment of the present invention, the stirring method is magnetic stirring, the stirring speed can be 300 rpm, and the time can be 1 h.

[0042] After the mixing is completed, the present invention also preferably includes filtering, and the filtering is preferably performed using a 0.45 μm organic membrane. In the present invention, the purpose of the filtering is to remove unnecessary impurities in the solution.

[0043] In the present invention, the concentration of cyclodextrin in the mixed solution is 2.5-12.5 mmol / L, preferably 5-10 mmol / L; the concentration of potassium hydroxide in the mixed solution is 20-100 mmol / L, preferably 40-80 mmol / L. In an embodiment of the present invention, the concentration of cyclodextrin in the mixed solution may be 2.5 mmol / L, 5 mmol / L or 12.5 mmol / L; the concentration of potassium hydroxide in the mixed solution may be 20 mmol / L, 40 mmol / L or 100 mmol / L.

[0044] After obtaining the mixed liquid, the present invention heats the mixed liquid in an environment of a first anhydrous ethanol, and then adds a second anhydrous ethanol to the mixed liquid to obtain the nano-scale cyclodextrin metal organic framework; the second anhydrous ethanol is added through a peristaltic pump; the rotation speed of the peristaltic pump is 25 to 100 rpm; the mixed liquid and the first anhydrous ethanol are not in direct contact.

[0045] In an embodiment of the present invention, the purity of the first anhydrous ethanol and the second anhydrous ethanol are both 99.8%.

[0046] In the present invention, the process of heating the mixed liquid in the environment of the first anhydrous ethanol is preferably to place the mixed liquid in a first container, then place the first container in a second container filled with the first anhydrous ethanol, and then place the first container in an oven for heating; the volume of the first container is smaller than that of the second container. In the present invention, the second container is preferably a closed environment.

[0047] In the present invention, the volume ratio of the mixed liquid to the first anhydrous ethanol is preferably (1-3): (2-10), more preferably (1-3): 5. In an embodiment of the present invention, the volume ratio of the mixed liquid to the first anhydrous ethanol may be 2:5.

[0048] In the present invention, the heating temperature is preferably 50-90°C, more preferably 60°C; the heating time is preferably 24-72h, more preferably 68h. In an embodiment of the present invention, the heating temperature may be 60°C, and the heating time may be 68h.

[0049] In the present invention, the above operations are used to realize the nucleation and partial growth process of the crystal.

[0050] In the present invention, the second anhydrous ethanol is preferably added via a peristaltic pump; the rotation speed of the peristaltic pump is preferably 25 to 100 rpm, more preferably 40 to 60 rpm. In an embodiment of the present invention, the rotation speed of the peristaltic pump may be 25 rpm, 50 rpm or 100 rpm.

[0051] In the present invention, the volume ratio of the mixed liquid to the second anhydrous ethanol is preferably (1-2):(1-2), more preferably 1:(1-2). In an embodiment of the present invention, the volume ratio of the mixed liquid to the second anhydrous ethanol may be 5:6.

[0052] In the present invention, the role of adding the second anhydrous ethanol in the above manner is to achieve secondary nucleation of crystals and end the growth of crystals to cause them to precipitate.

[0053] After the second anhydrous ethanol is added, the present invention also preferably includes centrifugation, washing and drying in sequence. In the present invention, the speed of the centrifugation is preferably 3000-6000rpm, more preferably 4000rpm, and the time of the centrifugation is preferably 5-20min, more preferably 10min. In an embodiment of the present invention, the speed of the centrifugation can be 4000rpm, and the time can be 10min. In the present invention, the washing is preferably carried out with anhydrous ethanol, and the number of washings is preferably 0-2 times. In an embodiment of the present invention, the time of the washing can be 0 times, 1 time or 2 times. In the present invention, the drying method is preferably vacuum drying, and the temperature of the vacuum drying is preferably 30-60°C, more preferably 40°C, and the time is preferably 4-12h, more preferably 5-10h. In an embodiment of the present invention, the temperature of the vacuum drying can be 40°C, and the time can be 8h. In the present invention, the number of ethanol washings may directly affect the crystal growth through the reversible transition layer at the crystal growth interface. As the number of ethanol washings increases, the size of the nano-cyclodextrin metal organic framework becomes more uniform.

[0054] In the present invention, the particle size of the nano-cyclodextrin metal organic framework is preferably 200 to 800 nm.

[0055] The present invention also provides a method for preparing a silver-doped nanoscale cyclodextrin metal organic framework (AgNPs@CD-MOFs), comprising the following steps:

[0056] After mixing the nano-cyclodextrin metal organic framework dispersion and the silver nitrate solution, the mixture is cultured in the dark to obtain the silver-doped nano-cyclodextrin metal organic framework;

[0057] The nano-cyclodextrin metal-organic framework in the nano-cyclodextrin metal-organic framework dispersion is a nano-cyclodextrin metal-organic framework dispersion prepared by the preparation method described in the above technical solution.

[0058] In the present invention, the solvent of the nano-cyclodextrin metal organic framework dispersion is preferably anhydrous ethanol. In the present invention, the concentration of the nano-cyclodextrin metal organic framework in the nano-cyclodextrin metal organic framework dispersion is preferably 1 to 20 mg / mL, more preferably 5 mg / mL. In an embodiment of the present invention, the concentration of the nano-cyclodextrin metal organic framework in the nano-cyclodextrin metal organic framework dispersion can be 5 mg / mL.

[0059] In the present invention, the solvent of the silver nitrate solution is preferably ethanol. In the present invention, the concentration of the silver nitrate solution is preferably 0.5 to 5 mmol / L, more preferably 1 mmol / L. In an embodiment of the present invention, the concentration of the silver nitrate solution may be 1 mmol / L.

[0060] In the present invention, the mass ratio of the nano-cyclodextrin metal-organic framework in the nano-cyclodextrin metal-organic framework dispersion to the silver nitrate in the silver nitrate solution is preferably (10-50): 1, more preferably (20-40): 1. In an embodiment of the present invention, the mass ratio of the nano-cyclodextrin metal-organic framework in the nano-cyclodextrin metal-organic framework dispersion to the silver nitrate in the silver nitrate solution may be 30:1.

[0061] In the present invention, the culture is preferably carried out under shaking conditions, the shaking frequency is preferably 50-200 rpm, more preferably 120 rpm; the time is preferably 12-72 h, more preferably 48 h. In an embodiment of the present invention, the culture frequency can be 120 rpm, and the time can be 48 h.

[0062] In the present invention, the in-situ reduction of silver ions to generate nanosilver occurs during the culture process.

[0063] After the cultivation is completed, the present invention also preferably includes centrifugation, washing and drying performed in sequence; in the present invention, the speed of the centrifugation is preferably 3000-6000rpm, more preferably 4000rpm, and the time of the centrifugation is preferably 5-20min, more preferably 10min. In an embodiment of the present invention, the speed of the centrifugation can be 4000rpm, and the time can be 10min. In the present invention, the washing is preferably carried out with anhydrous ethanol, and the number of washings is preferably 2 times. In the present invention, the drying method is preferably vacuum drying, and the temperature of the vacuum drying is preferably 30-60°C, more preferably 40°C, and the time is preferably 4-12h, more preferably 5-10h. In an embodiment of the present invention, the temperature of the vacuum drying can be 40°C, and the time can be 8h.

[0064] In the present invention, the silver-doped nano-cyclodextrin metal organic framework preferably comprises a nano-cyclodextrin metal organic framework and silver loaded in the nano-cyclodextrin metal organic framework. In the present invention, the silver is preferably a silver nanosheet. In the present invention, the loading amount of the silver is preferably 0.05wt% to 3.01wt%. In an embodiment of the present invention, the loading amount of the silver can be 3.01wt%.

[0065] The present invention also provides the use of the silver-doped nano-cyclodextrin metal organic framework prepared by the preparation method described in the above technical solution in food preservative film.

[0066] The present invention also provides a food preservative film, the preparation raw materials of which include silver-doped nano-cyclodextrin metal organic framework, polylactic acid and polyethylene glycol;

[0067] The mass ratio of the silver-doped nano-cyclodextrin metal organic framework, polylactic acid and polyethylene glycol is (0.2-1.6):8:0.8.

[0068] In the present invention, the polyethylene glycol is preferably PEG-4000.

[0069] In the present invention, the preparation method of the food preservative film preferably comprises the following steps:

[0070] mixing polylactic acid and an organic solvent to obtain a homogeneous solution;

[0071] The homogeneous solution, polyethylene glycol and silver-doped nano-cyclodextrin metal organic framework are mixed and then formed into a film to obtain the food preservative film.

[0072] The invention mixes polylactic acid and an organic solvent to obtain a homogeneous solution.

[0073] In the present invention, the organic solvent preferably includes dimethyl carbonate.

[0074] In the present invention, the usage ratio of the polylactic acid to the organic solvent is preferably (6-12) g:100 mL, more preferably (6-10) g:100 mL. In an embodiment of the present invention, the usage ratio of the polylactic acid to the organic solvent may be 8 g:100 mL.

[0075] In the present invention, the mixing is preferably carried out under stirring. In the present invention, the stirring temperature is preferably 60-100°C, more preferably 70°C, the stirring speed is preferably 300-800rpm, more preferably 500rpm, and the stirring time is preferably 2-5h, more preferably 3h. In an embodiment of the present invention, the stirring temperature can be 70°C, the time can be 3h, and the speed can be 500rpm.

[0076] After obtaining the homogeneous solution, the present invention mixes the homogeneous solution, polyethylene glycol and silver-doped nano-cyclodextrin metal organic framework to form a film, thereby obtaining the food preservative film.

[0077] In the present invention, the mixing is preferably adding melted polyethylene glycol and silver-doped nano-cyclodextrin metal organic framework in the homogeneous solution in sequence. After adding the melted polyethylene glycol, the present invention also preferably includes stirring, and the stirring temperature is preferably 60-100°C, more preferably 70°C, the stirring speed is preferably 300-800rpm, more preferably 500rpm, and the stirring time is preferably 2-5h, more preferably 3h. In an embodiment of the present invention, the stirring temperature can be 70°C, the time can be 3h, and the speed can be 500rpm. The present invention does not have any special restrictions on the method of adding the melted polyethylene glycol and silver-doped nano-cyclodextrin metal organic framework, and can be carried out by methods well known to those skilled in the art.

[0078] The present invention does not have any special limitation on the film forming process, and the film forming process may be carried out using a process well known to those skilled in the art.

[0079] The preparation method and application of CD-MOFs and AgNPs@CD-MOFs and food preservative film provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the scope of protection of the present invention.

[0080] Example 1

[0081] Dissolve γ-cyclodextrin and potassium hydroxide in ultrapure water, stir magnetically for 1 h (rotation speed is 300 rpm), and filter with a 0.45 μm organic membrane to obtain a mixed solution (the concentration of γ-cyclodextrin is 2.5 mmol / L, and the concentration of potassium hydroxide is 20 mmol / L);

[0082] 10 mL of the mixed solution was placed in a small vial, and then placed in a large glass bottle containing 25 mL of anhydrous ethanol. After drying at 60°C for 68 h, 12 mL of anhydrous ethanol was added to the small glass bottle at a speed of 25 rpm using a peristaltic pump. After centrifugation at 4000 rpm for 10 min, the obtained precipitate was washed twice with anhydrous ethanol, and then vacuum dried at 40°C for 8 h to obtain γ-CD-MOFs (white crystalline powder).

[0083] Example 2

[0084] Refer to Example 1, except that the rotation speed of the peristaltic pump is 50 rpm.

[0085] Example 3

[0086] Refer to Example 1, except that the rotation speed of the peristaltic pump is 100 rpm.

[0087] Example 4

[0088] Refer to Example 1, except that the concentration of γ-cyclodextrin in the mixed solution is 5 mmol / L, and the concentration of potassium hydroxide is 40 mmol / L.

[0089] Example 5

[0090] Refer to Example 4, except that the rotation speed of the peristaltic pump is 50 rpm.

[0091] Example 6

[0092] Refer to Example 4, except that the rotation speed of the peristaltic pump is 100 rpm.

[0093] Example 7

[0094] Refer to Example 1, except that the concentration of γ-cyclodextrin in the mixed solution is 12.5 mmol / L, and the concentration of potassium hydroxide is 100 mmol / L.

[0095] Example 8

[0096] Refer to Example 7, except that the rotation speed of the peristaltic pump is 50 rpm.

[0097] Example 9

[0098] Refer to Example 7, except that the rotation speed of the peristaltic pump is 100 rpm.

[0099] Example 10

[0100] Refer to Example 5, except that the number of washings with anhydrous ethanol is 0.

[0101] Embodiment 11

[0102] Refer to Example 5, except that the number of times of washing with anhydrous ethanol is 1 time.

[0103] Figure 1The scanning electron microscope (SEM) images, transmission electron microscope (TEM) images and energy dispersive X-ray spectroscopy (EDS) images of the γ-CD-MOFs described in Examples 1 to 11, wherein (a) is the SEM image of the γ-CD-MOFs described in Example 1 at ×200 magnification, (b) is the SEM image of the γ-CD-MOFs described in Example 2 at ×200 magnification, and (c) is the SEM image of the γ-CD-MOFs described in Example 3 at ×200 magnification. , (d) is the SEM image of the γ-CD-MOFs described in Example 1 at ×10000, (e) is the SEM image of the γ-CD-MOFs described in Example 2 at ×10000, (f) is the SEM image of the γγ-CD-MOFs described in Example 3 at ×10000, (g) is the SEM image of the γ-CD-MOFs described in Example 4 at ×10000, (h) is the SEM image of the γ-CD-MOFs described in Example 5 at ×10 (i) is the SEM image of the γ-CD-MOFs described in Example 6 at ×10000, (j) is the SEM image of the γ-CD-MOFs described in Example 7 at ×10000, (k) is the SEM image of the γ-CD-MOFs described in Example 8 at ×10000, (l) is the SEM image of the γ-CD-MOFs described in Example 9 at ×10000, (m) is the SEM image of the γ-CD-MOFs described in Example 10 (n) is the SEM image of γ-CD-MOFs described in Example 11 at a magnification of ×10000, (o) is the TEM image of γ-CD-MOFs described in Example 5, (p) is the C element distribution map of γ-CD-MOFs described in Example 5, (q) is the O element distribution map of γ-CD-MOFs described in Example 5, and (r) is the K element distribution map of γ-CD-MOFs described in Example 5; Figure 1 It can be seen that the particle size of the γ-CD-MOFs prepared by the preparation method of the present invention is nanometer-scale and has a typical cubic structure. The optimal preparation conditions are that the concentration of γ-cyclodextrin in the mixed solution is 5 mmol / L, the concentration of potassium hydroxide is 40 mmol / L, the speed of the peristaltic pump is 50 rpm, and the coefficient of ethanol is 2 times. The particle size of the γ-CD-MOFs prepared under the above optimal preparation conditions is 200-800 nm (as shown in (h));

[0104] Figure 2TEM images of the γ-CD-MOFs described in Example 5 and the particle size distribution diagram of the γ-CD-MOFs described in Example 5, wherein (a) is a TEM image of the AgNPs@γ-CD-MOFs prepared using 6mM AgNO3 and dissolved in water, (b) is a TEM image of the AgNPs@γ-CD-MOFs prepared using 3mM AgNO3 and dissolved in water, and (c) is a TEM image of the AgNPs@γ-CD-MOFs prepared using 1mM AgNO3 and dissolved in water. TEM image of silver nanoparticles after D-MOFs dissolved in water, (d) is the lattice spacing image of silver nanoparticles after AgNPs@γ-CD-MOFs dissolved in water prepared by 1mM AgNO3, (e) is the high-magnification TEM image of silver nanoparticles after AgNPs@γ-CD-MOFs dissolved in water prepared by 1mM AgNO3, (f) is the particle size distribution image of silver nanoparticles after AgNPs@γ-CD-MOFs dissolved in water prepared by 1mM AgNO3, Figure 2 It can be seen that reducing the concentration of AgNO3 leads to a decrease in the size of the prepared nanosilver.

[0105] Examples 12 to 22

[0106] 10 mL of 1 mmol / L silver nitrate ethanol solution was added to 10 mL of 5 mg / mL anhydrous ethanol solution of the γ-CD-MOFs described in Examples 1 to 11, respectively, and the mixture was shaken (at a frequency of 120 rpm) and cultured for 48 h in the dark, and centrifuged at 4000 rpm for 10 min. The obtained precipitate was washed twice with anhydrous ethanol and dried in vacuo at 40° C. to obtain AgNPs@γ-CD-MOFs (AgNPs@γ-CD-MOFs prepared from the γ-CD-MOFs described in Examples 1 to 11 correspond to Examples 12 to 22, respectively);

[0107] Figure 3 The SEM image (a), TEM image (b), EDS image of a single AgNPs@γ-CD-MOFs (c), EDS point scan image of a single AgNPs@γ-CD-MOFs (d), EDS surface scan image of a single AgNPs@γ-CD-MOFs - C element distribution image (e), O element distribution image (f), K element distribution image (g) and Ag element distribution image (h) of the AgNPs@γ-CD-MOFs described in Example 16 are shown in FIG. Figure 3 It can be seen that the AgNPs@CD-MOFs maintain a typical cubic morphology, indicating that the in situ synthesis of silver nanoparticles will not destroy the basic structure of γ-CD-MOFs. In addition, except for a small amount of nanosilver aggregation on the surface, the remaining small nanosilver particles are evenly distributed in the γ-CD-MOFs framework.

[0108] The specific surface area and pore size distribution of the γ-CD-MOFs described in Example 1 and the AgNPs@γ-CD-MOFs described in Example 16 were determined by N2 adsorption-desorption method using a specific surface area and pore size analyzer (Micromeritics ASAP 2460, USA); wherein, Figure 4 The N2 adsorption-desorption curve (a) and pore size distribution curve (b) of the γ-CD-MOFs described in Example 1 and the AgNPs@γ-CD-MOFs described in Example 16 are shown in FIG. Figure 4 It can be seen that the reduction in the size of γ-CD-MOFs leads to a higher BET surface area, which further improves the loading capacity. In addition, due to the filling of effective pores by AgNPs, the BET surface area of ​​AgNPs@γ-CD-MOF is significantly reduced compared with that of γ-CD-MOFs;

[0109] The silver content of the AgNPs@γ-CD-MOFs described in Example 16 and the release of silver nanosheets from the AgNPs@γ-CD-MOFs in pure water were measured by inductively coupled plasma mass spectrometry (ICP-MS, Aglient 7850, USA). The loading amount of silver nanosheets in the AgNPs@γ-CD-MOFs described in Example 16 was 3.008% (3.01±0.06%, which was 3.86 times higher than that reported previously). The test results are shown in Table 1:

[0110] Table 1 Release of silver nanosheets from AgNPs@γ-CD-MOFs in pure water in Example 16

[0111] time Release percentage of silver in pure water (%) 3D 1.59±0.04 6D 2.12±1.10 10D 2.57±0.10

[0112] As shown in Table 1, the silver nanosheets released 2.57% after 10 days of release, which is lower than the release rate of the prior art.

[0113] Embodiment 23

[0114] 8 g of polylactic acid (PLA) was added to 100 mL of dimethyl carbonate (DMC) and stirred at 70 ° C for 3 h to obtain a homogeneous solution, and then 0.8 g of melted polyethylene glycol (PEG-4000) was added and stirred at 70 ° C for 2 h. 0.2 g of AgNPs@CD-MOFs described in Example 16 was added and mixed evenly. The obtained mixed slurry was formed into a film on the surface of a glass plate to obtain a food preservative film (referred to as F2 film).

[0115] Embodiment 24

[0116] 8 g of polylactic acid (PLA) was added to 100 mL of dimethyl carbonate (DMC) and stirred at 70 ° C for 3 h to obtain a homogeneous solution, and then 0.8 g of melted polyethylene glycol (PEG-4000) was added and stirred at 70 ° C for 2 h. 0.4 g of AgNPs@CD-MOFs described in Example 16 was added and mixed evenly. The obtained mixed slurry was formed into a film on the surface of a glass plate to obtain a food preservative film (referred to as F4 film).

[0117] Embodiment 25

[0118] 8 g of polylactic acid (PLA) was added to 100 mL of dimethyl carbonate (DMC) and stirred at 70 ° C for 3 h to obtain a homogeneous solution, and then 0.8 g of melted polyethylene glycol (PEG-4000) was added and stirred at 70 ° C for 2 h. 0.8 g of AgNPs@CD-MOFs described in Example 16 was added and mixed evenly. The obtained mixed slurry was formed into a film on the surface of a glass plate to obtain a food preservative film (referred to as F8 film).

[0119] Embodiment 26

[0120] 8 g of polylactic acid (PLA) was added to 100 mL of dimethyl carbonate (DMC) and stirred at 70 ° C for 3 h to obtain a homogeneous solution, and then 0.8 g of melted polyethylene glycol (PEG-4000) was added and stirred at 70 ° C for 2 h. 1.6 g of AgNPs@CD-MOFs described in Example 16 was added and mixed evenly. The obtained mixed slurry was formed into a film on the surface of a glass plate to obtain a food preservative film (referred to as F16 film).

[0121] Comparative Example 1

[0122] Referring to Example 23, the difference is that the addition of AgNPs@CD-MOFs is omitted to obtain a food preservative film (denoted as PLA film).

[0123] Comparative Example 2

[0124] Referring to Comparative Example 1, the difference is that PLA is replaced by PE to obtain a food preservative film (referred to as PE film).

[0125] Test Case

[0126] The antibacterial activity of the AgNPs@γ-CD-MOFs described in Example 16 was measured: Escherichia coli, Staphylococcus aureus, Bacillus subtilis, Pseudomonas aeruginosa and Pseudomonas aeruginosa were used to evaluate the antibacterial activity of the AgNPs@γ-CD-MOFs described in Example 16; the minimum inhibitory concentration (MIC) test method was: the broth microdilution method recommended by the Clinical and Laboratory Standards Institute (CLSI) standard M07 was adopted; the minimum bactericidal concentration (MBC) test method was: 100 μL of the bacterial suspension with a concentration of AgNPs@γ-CD-MOFs higher than the MIC described in Example 16 was inoculated into an agar medium, and after culturing for 24 hours, the sample concentration with less than 50 colonies was the minimum bactericidal concentration;

[0127] The cytotoxicity of the AgNPs@γ-CD-MOFs described in Example 16 was determined: undifferentiated human colon cancer cells (HT-29) were used to determine the cytotoxicity;

[0128] Cell viability test method: CCK-8;

[0129] The test results are as follows Figure 5 As shown in Table 2, Figure 5 The antibacterial activity (a) and cell viability (b) of AgNPs@γ-CD-MOFs described in Example 16 are shown in Table 1. Figure 5 As shown in (a), the AgNPs@γ-CD-MOFs described in Example 16 exhibited antibacterial activity against five bacteria, namely, Escherichia coli, Staphylococcus aureus, Bacillus subtilis, Pseudomonas aeruginosa, and Pseudomonas aeruginosa, and its antibacterial ability against Escherichia coli, Staphylococcus aureus, and Pseudomonas aeruginosa was significantly enhanced; Figure 5 As shown in (b), when the concentration of AgNPs@γ-CD-MOFs described in Example 16 is below 400 μg / mL, the cell viability is higher than 70% and has no cytotoxicity;

[0130] Table 2 shows the antibacterial activity of AgNPs@γ-CD-MOFs described in Example 16. It can be seen from Table 2 that AgNPs@γ-CD-MOF exhibits antibacterial activity against the selected five bacteria. Compared with existing reports, AgNPs@γ-CD-MOF reduces the MIC values ​​and MBC values ​​(based on actual silver content) of Escherichia coli, Staphylococcus aureus, and Pseudomonas aeruginosa, showing better antibacterial activity;

[0131] Table 2 Antibacterial activity of AgNPs@γ-CD-MOFs described in Example 16

[0132]

[0133]

[0134] The visible light and ultraviolet light transmittance of the food preservative films of Examples 23 to 26 were measured using an ultraviolet-visible spectrophotometer (scanning wavelength 200-800nm, resolution 120nm); the oxygen permeability of the film was measured using an air permeability tester (BTY-B2P, China Languang) (temperature 23±2°C, humidity 49±1%RH), and the water vapor permeability of the food preservative films was measured by a fabric moisture permeability tester (YG461E, China);

[0135] Figure 6 The visible light and ultraviolet light transmittance (a), water vapor transmittance (b) and oxygen transmittance (c) of the food preservative films of Examples 23 to 26 and Comparative Example 1 are: Figure 6 It can be seen that the addition of AgNPs@γ-CD-MOFs improves the UV barrier and oxygen barrier capabilities of the food preservative film. Except for Example 25, the addition of AgNPs@γ-CD-MOFs does not significantly change the water vapor barrier capability.

[0136] Antibacterial property of food preservative film: 0.5 g of the food preservative film described in Example 25 and Comparative Example 1 was mixed with 15 mL of physiological saline, sterilized at 121° C. for 20 min, cooled, added with 0.5 mL of bacterial suspension (106 CFU / mL), and fully shaken on a TY-70B shaker (Tianjin Test Instrument Co., Ltd.) for 1 hour (220 rpm, 37° C.) to ensure that the composite film was in full contact with the bacteria, and finally 0.1 mL of the supernatant was smeared on a nutrient agar medium, cultured at 37° C. for 24 h, the total bacterial colony count was tested, and the antibacterial rate was calculated; antibacterial rate = (N0-N) / N×100%, wherein N0 is the total cell colony count of the blank group (the blank group is the group without adding food preservative film), and N is the total bacterial colony count of the experimental group; Figure 7 The antibacterial rate of the food preservative film described in Example 25 and Comparative Example 1 against different types of bacteria is shown in the bar graph. Figure 7 It can be seen that after adding AgNPs@γ-CD-MOFs, the antibacterial properties of the film against Escherichia coli, Staphylococcus aureus, Pseudomonas aeruginosa, and Pseudomonas tora are significantly improved;

[0137] Fresh Agaricus bisporus was precooled in a constant temperature and humidity chamber at 4°C and 60% relative humidity for 24 hours, and then Agaricus bisporus with good appearance and uniform size were selected for subsequent storage and preservation. The mushrooms were randomly divided into six groups, with six pieces in each group, and then the mushrooms were placed in a disposable plastic box (polypropylene, 200×140×65mm) and sealed with the food preservative film described in Examples 23 to 26 and Comparative Examples 1 to 2, wherein the food preservative film described in Comparative Examples 1 to 2 was used as the control group. Finally, the packaged Agaricus bisporus was placed in a constant temperature and humidity chamber (4°C, 90% RH) for storage and preservation. Figure 8 For Agaricus bisporus preservation effect diagram, by Figure 8 It can be seen that compared with the food preservative films described in Comparative Examples 1 to 2, the food preservative films described in Examples 23 to 26 delayed the problem of post-harvest quality deterioration of Bacillus bisporus, especially the food preservative film described in Example 25 had the best preservation effect.

[0138] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a nanoscale cyclodextrin metal organic framework, characterized in that: The following steps are involved: Mixing cyclodextrin, potassium hydroxide and water to obtain a mixed solution; the concentration of cyclodextrin in the mixed solution is 2.5 to 12.5 mmol / L; the concentration of potassium hydroxide in the mixed solution is 20 to 100 mmol / L; After heating the mixed solution in the environment of the first anhydrous ethanol, adding the second anhydrous ethanol to the mixed solution to obtain the nano-cyclodextrin metal organic framework; the second anhydrous ethanol is added by a peristaltic pump; the rotation speed of the peristaltic pump is 25-100 rpm; The mixed liquid is not in direct contact with the first anhydrous ethanol.

2. The preparation method according to claim 1, characterized in that The molar ratio of the cyclodextrin to potassium hydroxide is 1:

8.

3. The preparation method according to claim 2, characterized in that: The mixing is carried out under stirring conditions; The stirring speed is 100-400 rpm, and the stirring time is 30-120 min.

4. The preparation method according to claim 1, characterized in that: The mixing further includes filtering; The filtration adopts a 0.45 μm organic membrane.

5. The preparation method according to claim 1, characterized in that: The heating temperature is 50-90° C. and the heating time is 24-72 hours.

6. A method for preparing a silver-doped nanoscale cyclodextrin metal organic framework, characterized in that: The following steps are involved: After mixing the nano-cyclodextrin metal organic framework dispersion and the silver nitrate solution, the mixture is cultured in the dark to obtain the silver-doped nano-cyclodextrin metal organic framework; The nano-cyclodextrin metal-organic framework in the nano-cyclodextrin metal-organic framework dispersion is a nano-cyclodextrin metal-organic framework dispersion prepared by the preparation method according to any one of claims 1 to 5.

7. The preparation method according to claim 6, characterized in that: The mass ratio of the nano-cyclodextrin metal organic framework in the nano-cyclodextrin metal organic framework dispersion to the silver nitrate in the silver nitrate solution is (10-50):

1.

8. The preparation method according to claim 6, characterized in that: The culture is carried out under shaking conditions, the frequency of the shaking is 50 to 200 rpm, and the time is 12 to 72 hours.

9. Use of the silver-doped nano-cyclodextrin metal organic framework prepared by the preparation method according to any one of claims 6 to 8 in food preservative film.

10. A food preservative film, characterized in that: The preparation raw materials include silver-doped nano-sized cyclodextrin metal organic framework, polylactic acid and polyethylene glycol; The mass ratio of the silver-doped nano-cyclodextrin metal organic framework, polylactic acid and polyethylene glycol is (0.2-1.6):8:0.8.

Citation Information

Patent Citations

  • Preparation method, product and application of gamma-cyclodextrin metal organic framework @ cellulose fiber composite material

    CN110511392A

  • Preparation method and application of fruit biological fresh-keeping film of curcumin-loaded gamma-CD-MOFs

    CN115651232A

  • Gamma-cyclodextrin metal organic framework and preparation method thereof

    CN115772271A